The Impact of Inter-provincial Migration on the Labor Market Outcomes in Two Developed Provinces in South Africa - Kleinhans, Joseph; Yu, Derek (African Human Mobility Review, 2021)
This study used the South African Census 2011 data to examine the impact of interprovincial migration on the labor market outcomes in the Western Cape and Gauteng, the two most developed and popular inter-provincial migration destination provinces in South Africa. In both provinces, the residents were divided into four groups: permanent residents, intra-provincial migrants, long-term inter-provincial migrants and short-term inter-provincial migrants. The descriptive statistics indicated that both short- and long-term inter-provincial migrants into the two provinces were likely to be young people aged 15-34 years, unmarried African urban residents with 11-12 educational years on average, coming from households with three members. These interprovincial migrants enjoyed lower unemployment rates than the permanent residents, but the intra-provincial migrants remained the best-performing group with the lowest unemployment rate and highest share of employed persons involved in formal sector activities. The study also conducted a multivariate econometric analysis with probit regressions on labor force participation likelihood, and Heckprobit regressions on employment likelihood (conditional on labor force participation). After controlling for differences in other characteristics (or ceteris paribus), compared to the permanent residents, it was evident that both short- and long-term inter-provincial migrants into Western Cape and Gauteng were about 3% significantly more likely to be employed. After examining migrants from the Eastern Cape to the Western Cape and migrants from Limpopo to Gauteng, the study found that both groups enjoyed a much higher labor force participation rate (above 70%) and lower unemployment rate (30%), compared to individuals who remained in the Eastern Cape and Limpopo (labor force participation rate: 45%; unemployment rate: 38%).